Invisible ink my mother's secret love affair with a famous cartoonist ; a graphic memoir - Griffith, Bill 1944- (Fantagraphics Books, 2015)
"Fifteen minutes after Bill Griffith's father died from a bicycle accident in 1972, his mother turned to him and said, "If I don't tell you this now, I'll never be able to tell you. I had a long and happy relationship with a man you knew slightly." Thus began Griffith's journey to reconstruct this hidden relationship between his mother and a deeply cultured jack-of-all-trades cartoonist and crime novelist. Invisible Ink unfolds like a detective story, alternating between past and present, as Griffith recreates the quotidian habits of suburban Levittown and the professional and cultural life of Manhattan in the 1950s and '60s as seen through his mother's and his own teenage eyes. Griffith finally discovers the holy grail of his mother's past: her diary, an ecstatic evocation of her sexual liaison, and an eloquent testament to her deepest feelings; and an unfinished novel that parallels the trajectory of her own life. Griffith puts the pieces together and reveals a mother he never knew" --
Keywords: Griffith, Bill -- 1944- -- Family; Mothers and sons -- Comic books, strips, etc; Parent and adult child -- Comic books, strips, etc; Adultery -- Comic books, strips, etc; Comic books, strips, etc -- United States; Sohn; Beziehung; Ehebruch; Mutter; New York, NY; Comic